2016
DOI: 10.1002/mds.26482
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic A daptive D eep B rain S timulation for R esting T remor in P arkinson's D isease

Abstract: References1. Rango M, Arighi A, Bresolin N. Brain temperature: what do we know? Neuroreport 2012;23:483-487. 2. Rango M, Arighi A, Bonifati C, Bresolin N. Increased brain temperature in Parkinson disease. Neuroreport 2012;23:129-133. 3. Powers WJ, Videen TO, Markham J. Cerebral mitochondrial metabolism in early Parkinson's disease. J Celeb Blood Flow Metab 2008;28:1754-1760. 4. Jezek J, Jaburek M, Zelenka Y, Jezek P. Mitochondrial phospholipase A 2 activated by reactive oxygen species in heart mitochondria ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 8 publications
0
100
1
Order By: Relevance
“…Activa PC+S can also be used to prototype feedback-controlled DBS algorithms, guided either by brain recording, or external sensors 15 . Feedback control may improve DBS therapy by real time-adjustment of stimulation parameters in response to fluctuating signs and symptoms 14,28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activa PC+S can also be used to prototype feedback-controlled DBS algorithms, guided either by brain recording, or external sensors 15 . Feedback control may improve DBS therapy by real time-adjustment of stimulation parameters in response to fluctuating signs and symptoms 14,28 .…”
Section: Discussionmentioning
confidence: 99%
“…This device, Activa PC+S ( Medtronic, Inc ), allows chronic, intermittent collection of field potential data over years, initiated either by investigators in the clinic, by patients in their homes, or by automated algorithms 1,2,30,32,33 . The device is available to research groups worldwide under investigator-initiated protocols, or under CE Mark in European countries 15,20,27 . In our study, the stimulation/sensing pulse generator is attached to both a basal ganglia and a cortical electrode array, to allow multisite recordings for network-level analyses.…”
Section: Introductionmentioning
confidence: 99%
“…However, the activity-dependent fluctuations in the beta-band power limit its use a sole control for closed loop DBS in PD tremor. Bronte-Stewart and colleagues (Malekmohammadi et al, 2016) reported the efficacy of closed loop STN DBS to control resting tremor, using a kinematic measure of tremor power from use of a wearable Bluetooth enabled smart watch (LG G-watch; Figure 5). …”
Section: Closed-loop Dbsmentioning
confidence: 99%
“…Case studies in Parkinson’s disease [37] and essential tremor [38] suggest the feasibility of using wearable sensors. One downside of this approach is that the system will only be able to suppress symptoms after they manifest, and neural signals would be likely to neuromodulate prior to a clinical manifestation.…”
Section: Development Of Closed-loop Dbs Systemsmentioning
confidence: 99%